The Effect of Smartphone Use on Students' Intensive Reading Achievement - Tuminah; Julis (Journal of Educational Analytics, 2022)
The purpose of this study was to describe the effect of the use of Smartphones on the students’ achievement of Intensive Reading learning in St Augustine Hippo Catholic University. The development of information technology has been so fast, that it has affected every aspect of human life. In addition, the development of information and communication technology has a positive impact on humans but it can also have a negative impact, especially on mobile communication devices (smartphones). The method used in this research is a quantitative research survey design. The research findings indicate several important points, namely: (1) Improvement of students' learning achievement in Intensive Reading, (2) Students are more active in conducting learning activities in class, and (3) The quality of teaching and learning process increases significantly. It can be concluded that the use of a Smartphone could increase students’ achievement.